Pengaruh Pengawasan dan Kepuasan Kerja Terhadap Disiplin Kerja pada Kantor Pertanahan Kabupaten Bima - Nursakinah, Nursakinah; Hidayanti, Mawar; Aprianti, Kartin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the influence of supervision and job satisfaction on employee work discipline at the Land Office of Bima Regency. Specifically, it examines: (1) the effect of supervision on work discipline, (2) the effect of job satisfaction on work discipline, and (3) the joint effect of supervision and job satisfaction on work discipline. This research employed an associative quantitative approach. The population comprised 62 employees, consisting of 30 civil servants (ASN), 3 government contract employees (PPPK), and 29 permanent honorary staff, all of whom were included as the sample. Data were collected using observation sheets and Likert-scale questionnaires. The analysis involved validity and reliability tests, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), multiple regression analysis, correlation and determination coefficients, as well as simultaneous and partial tests. The findings indicate that: (1) supervision has a significant effect on work discipline, (2) job satisfaction has a significant effect on work discipline, and (3) supervision and job satisfaction jointly have a significant effect on work discipline among employees of the Land Office of Bima Regency.